Cooperative multi-attribute bilateral online negotiation for e-commerce - ZHAO, Lei (Institutional Knowledge at Singapore Management University, 2001)
Currently, fixed-price sale and online auction are two major sale modes in the applied electronic commerce systems. Bilateral negotiation does not yet have a satisfying performance in the Internet-based transactions. In this paper, the time-independent feature of online negotiations is emphasized. Correspondingly, a formal mathematical model of online negotiation is established. We also present a flexible and feasible bilateral negotiation protocol which is used in an agent-based cooperative negotiation. The protocol guarantees that any achieved deal is a Pareto optimal result. In addition, an improved approach to make the negotiating process rapidly converge on a deal is discussed in the paper.